Legal Regulation of Non-State Participation in Municipal Social Services in Lithuania - Andrius Stasiukynas; Aušra Šukvietienė; Justinas Staliūnas; Svajonė Rainienė; Danguolė Micutienė (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2025)
This study explores the role of non-state actors in Lithuania’s social service sector, a field shaped by demographic change, growing demand, and governance reforms. While national legislation provides opportunities for non-governmental organisations (NGOs) to participate in service delivery, planning, and oversight, the practical implementation of these provisions varies across municipalities. Using document analysis and secondary statistical data, the paper compares two municipalities Marijampolė and Alytus to examine how the legal framework is applied locally. The findings show that national regulation has expanded the formal space for NGO involvement through accreditation, diversified funding, and defined provider requirements. However, municipal differences in infrastructure, administrative capacity, and policy priorities produce distinct cooperation models: Marijampolė demonstrates more established NGO engagement, while Alytus shows a gradual, incremental approach. Overall, the study reveals persistent fragmentation and uneven implementation, highlighting the need for coherent mechanisms to strengthen multi actor collaboration in social service provision.